Recommendation and implementation of good practice in researcher evaluation in Finland - Pölönen, Janne (Septentrio Conference Series, 2021)
See RECORDING. Finland is among the first countries to have developed national recommendation on responsible research assessment in 2020. Recommendation for the Responsible Evaluation of a Researcher in Finland provides a set of general principles (transparency, integrity, fairness, competence, and diversity), which apply throughout 13 recommended good practices to improve four aspects of researcher evaluation: A) Building the evaluation process; B) Evaluation of research; C) Diversity of activities; and D) Researcher’s role in the evaluation process. The national recommendation was produced by a broad-based working-group constituted by the Federation of Finnish Learned Societies, however the implementation needs to take place at institutions, which all have their diverse circumstances, challenges, needs and goals. The national recommendation has an implementation plan, which includes development of national level infrastructures and services to support more qualitative and diverse assessments policies and practices locally. The institutional uptake of the recommendation will be promoted by forthcoming National policy and executive plan for open scholarship, and tracked across all research performing organisations as a part of biannual Open Science monitoring exercise starting in 2022.